PENGARUH KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWA MELALUI MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING ( STUDI PADA KARYAWAN PT PGAS SOLUTION JAKARTA ) - Sirait, Fathihari Afkha; Budiatmo, Agung (Jurnal Ilmu Administrasi Bisnis, 2019)
One of the most important resources of a company is human resources or the employees andÂ  every company needs to think the way to improve the performance of employees they have in order to drive the company's progress. One of the key to improve employee performance is by maintaining employee motivation. There are many factors that can increase work motivation and employee performance such as compensation factors and work environment conditions. This study aims to determine the effect of compensation and work environment on employee performance through work motivation on employees of PT PGAS Solution Jakarta. The type this research is using explanatory research. Sampling is using non-probability sampling techniques with saturated sampling approach of 80 respondents. The data were collected by some techniques such as questionnaires, interviews, and literature study. Data analysis method is using regression analysis with the help of IBM SPSS version 24.0 and Sobel test analysis. The results showed that there was an effect of compensation on work motivation, there was an effect of compensation on employee performance, there was an influence of work environment on work motivation, there was an influence of work environment on employee performance, there was an effect of work motivation on employee performance. There is an effect of compensation and work environment on work motivation. Based on the sobel test results, there is the effect of compensation on employee performance through work motivation and work environment on employee performance through work motivation. Based on the results of the mediation test, work motivation is a partial intervening variable in mediating the effect of compensation on employee performance and work motivation is a partial intervening variable in mediating the effect of the work environment on employee performance. The advice given to PT PGAS Solution is to improve the provision of compensation, such as considering employee input regarding the principal salary policy and leave procedures. Improve the work environment by improving work facilities, making regulations that regulate noise at work, increasing the level of security and carrying out activities to strengthen relationships between employees, and increase employee morale.